2002
DOI: 10.1146/annurev.pharmtox.42.091901.115838
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Function, and Inhibition of Chemokines

Abstract: Chemokines are the largest family of cytokines in human immunophysiology. These proteins are defined by four invariant cysteines and are categorized based on the sequence around the first two cysteines, which leads to two major and two minor subfamilies. Chemokines function by activating specific G protein-coupled receptors, which results in, among other functions, the migration of inflammatory and noninflammatory cells to the appropriate tissues or compartments within tissues. Some of these proteins and recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
498
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 560 publications
(514 citation statements)
references
References 172 publications
7
498
0
4
Order By: Relevance
“…N-terminal-truncated or modified chemokine analogs have been reported to act as receptor antagonists (for review, see ref. 25). To examine the role of the N-terminal region of murine IP-10 in determining func- tionality, we designed a series of analogs that were shortened at the N-terminal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…N-terminal-truncated or modified chemokine analogs have been reported to act as receptor antagonists (for review, see ref. 25). To examine the role of the N-terminal region of murine IP-10 in determining func- tionality, we designed a series of analogs that were shortened at the N-terminal.…”
Section: Resultsmentioning
confidence: 99%
“…In chemokines it has been observed that the N-terminal region is essential for functional activity and that the loop immediately following the first 2 cysteines in the sequence, as well as the N-terminal region, has an important role in receptor binding (25). Truncation or modification of a few N-terminal amino acids in several chemokines, such as MCP-1, MCP-2, RANTES, IL-8, Fkn, and secondary lymphoid-tissue chemokine/CCL21, has been reported to lead to significant changes in functional activity and receptor binding (11,24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CXC chemokines can be subdivided into two groups based on the presence of the Glu-Leu-Arg (ELR) motif which is critical for receptor binding and signaling [3,4]. The chemokines containing the ELR motif (ELR + ) like IL-8 preferentially attract neutrophils, while the CXC chemokines without an ELR motif (ELR À ) mainly attract lymphocytes and monocytes [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…1 In screening a proprietary chemical library, 2 we recently identified compounds belonging to the chalcone family and preventing CXCL12 from binding to its CXCR4 or CXCR7 receptors. 3 These compounds have an original mechanism of action: they bind to the chemokine rather than to the receptors.…”
mentioning
confidence: 99%